(3GdBKGQ GdHGbjI Yf GdbQhf GdNGdjIs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJYGdi Yf GdGVGO hGdGTHGg hHYO abO SCdfi CMO GdGOHGA Yf GdJhGQjN GdJi jSJYedgG GdGee hGdGNJdGa GdhGbY ai GdGUhd GdJi gi eHGOjgG s
(3BNQgG (B:s
(3hdfNJe BNQ GdcJGH HGdMeO ddg GdPi fUQ hgOi hChVM SHjd GdQTO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG GdYOjO ef GdLOhGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B9s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdadcs